Meta-analysis of bovine Varicellovirus bovinealpha1 (BoAHV-1) prevalence in Türkiye and economic relevance - Arikan, Mehmet Saltuk; Mat, Burak; Cevrimli, Mustafa Bahadir; Dogan, Firat; Akin, Ahmet Cumhur; Tekindal, Mustafa Agah (Bmc, 2026)
Background Varicellovirus bovinealpha1 (BoAHV-1) is among the most important infectious agents affecting cattle health and productivity. This study aimed to determine the seroprevalence of BoAHV-1 infection in T & uuml;rkiye and estimate its economic impact using a meta-analytical approach. Results A total of 39 studies comprising data from 5,219 animals were included in the meta-analysis. Three analytical groups were established based on sample size and study scale: the small-scale group (SSG), large-scale group (LSG), and herd-level group (HLG). Random effects models were used for prevalence estimation, and heterogeneity was assessed using the Q, I-2, and tau(2) statistics. Publication bias was evaluated via Egger's regression and Kendall's Tau tests. The pooled prevalence was estimated at 0.320 for the SSG group, 0.427 for the LSG group, and 0.356 for the HLG group. The highest level of heterogeneity was identified in the LSG group (I-2 = 99.76%). The economic impact of BoAHV-1 was evaluated under two distinct scenarios-one incorporating abortion-related losses and the other excluding them. Principal components of loss included reduced milk production, live weight reduction, delayed onset of first calving, prolonged calving intervals, and losses attributable to aborted calves. The average total economic loss per infected animal was estimated to range from 285.18 to 383.21 USD. Conclusion These findings suggest a dynamic epidemiological pattern and a potentially high economic burden of BoAHV-1 infection in T & uuml;rkiye, highlighting the need for effective herd-level control and prevention measures.
Keywords: Bovine herpesvirus 1; Economic losses; Dairy cattle; Meta-analysis; T & uuml;rkiye; Varicellovirus bovinealpha1